2018
DOI: 10.1055/s-0038-1667169
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Resected Non-small Cell Lung Cancer with Ipsilateral Pulmonary Metastasis

Abstract: There was no significant difference in survival between T3 and T4 patients. Among surgically treated patients due to NSCLC, poor prognostic factors were advanced age for the patients with PM, nodule size and AC for T3 patients, and the number of nodules for T4 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…The 5-year OS of 56.1% for T3-Add patients in the current study seems to be a little higher than approximately 47% in the IASLC study, 9 but the survival was comparable with 52.9–55.0% in previous studies. 7,16,17 The 5-year OS for T4-Add patients was 43.4% in our study, which was comparable to nearly 40% in the IASLC study and 37.2% of Ucvet and his colleagues’ study 9,18…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The 5-year OS of 56.1% for T3-Add patients in the current study seems to be a little higher than approximately 47% in the IASLC study, 9 but the survival was comparable with 52.9–55.0% in previous studies. 7,16,17 The 5-year OS for T4-Add patients was 43.4% in our study, which was comparable to nearly 40% in the IASLC study and 37.2% of Ucvet and his colleagues’ study 9,18…”
Section: Resultssupporting
confidence: 80%
“… 8 , 16 , 31 Only in Ucvet and his colleagues’ study, T4-add patients with two or more nodules were reported to have a significantly worse prognosis ( p = 0.01) but the sample size of this study was relatively low ( N = 27). 18 In the current study, there were 25.5% (37/145) and 16.7% (29/174) patients with two or more additional nodules in the T3-Add and T4-Add patients, respectively. And the number of additional nodules did not show a significant effect on prognosis of T3-Add patients (two or more nodules versus one nodule, HR, 1.153, 95% CI, 0.694–1.918, p = 0.582) and T4-Add patients (two or more nodules versus one nodule, HR, 1.230, 95% CI, 0.758–1.997, p = 0.402).…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Lung adenocarcinoma (LUAD) is the most common histological type of NSCLC. Despite significant progress in lung adenocarcinoma therapeutic methods, including surgical treatment, target therapy, and early cancer detection, the overall LUAD survival rate remains low [ 3 ]. Currently, cytology screening and imaging examination are sensitive cancer screening tools, but they are not effective for the early detection of lung adenocarcinoma [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%